SISTEM INFORMASI MANAJEMEN PENDIDIKAN: PENERIMAAN PESERTA DIDIK BARU (PPDB) DI MTS NURUL HUDA KAB TANGERANG - Arlan, Fadilah Salsabila; Hasanah, Yenny Merinatul; Mardiana, Sri (Jurnal Multidisipliner Kapalamada, 2025)
The development of information technology has encouraged digital transformation in educational institutions to improve management efficiency and transparency. This study aims to evaluate the implementation of education management information systems in the process of Admission of New Learners (PPDB) at MTs Nurul Huda, Tangerang. Using a qualitative approach, data were collected through direct observation, interviews with stakeholders, and documentation studies. The results showed that the PPDB information system successfully simplified the management of prospective students' data, accelerated the administrative process, and improved information accountability. The implementation of this system also reduces manual errors and increases transparency in learner selection. However, challenges such as limited infrastructure and HR competencies in operating the system still need attention. The findings of this study recommend continuous training for system operators and the development of more user-friendly features to optimize the benefits of information systems in education management. This study makes an important contribution in understanding the impact of digitalization on the efficiency of the PPDB process at the madrasah level.